Evaluation of marker assisted backcross breeding derived lines for morpho-physiological characters under late sown heat stress condition in bread wheat - Amasiddha, B.; Ramya, K.T.; Kumar, C Prashant; Neha, R.; Leena, T.; krishna, Hari; Ramya, P.; Jain, N.; Singh, P.K.; Singh, G.P.; Prabhu, K.V. (The Indian Journal of Genetics and Plant Breeding, 2016)
An experiment was conducted to study the performance of  BC2F3 and BC1F4 lines derived in marker assisted backcross breeding (MABB) program for different morphological and physiological traits under late sown conditions. Two QTLs were introgresed into HD2733, one for days to anthesis and other for yield under stress conditions from an identified heat tolerant variety WH730 (donor). The lines were subjected to heat stress by sowing late in the season and the data was recorded on several characters at different phenological stages. A significant difference (P